Controlling the aggregation and assembly of boron‐containing molecular and polymeric materials. Issue 2 (20th January 2022) - Shimoyama, Daisuke; Jäkle, Frieder
Abstract: Boron‐containing molecules and polymers are attractive as powerful tunable Lewis acids for small molecule activation and catalysis, as luminescent materials for organic electronic device and (bio)imaging applications, and as smart chemical sensors. While the characteristics of the boron‐containing building blocks are attractive in and of themselves, their assembly into higher order supramolecular materials offers access to unique properties and emerging functions. Herein, we highlight recent achievements in the field of aggregated organoboron materials. We discuss how supramolecular interactions can be exploited to precisely control the structure of the assemblies and impact their functions as luminescent materials, recyclable and smart catalyst systems, chemical sensors, stimuli‐responsive and self‐healing materials. Abstract : This review summarizes the key strategies for precisely controlling the structure and function of aggregated organoboron materials while introducing some of the most recent advances in the field. Molecular aggregation and self‐assembly processes lead to well‐ordered structures with unique properties and functions. The electron‐deficient characteristics of the organoboron building blocks are exploited to develop fascinating new materials.